SHOOT, TOTAL PHENOLIC, AND ANTHOCYANIN PRODUCTION OF Plectranthus amboinicus WITH ORGANIC FERTILIZING - Ekawati, Rina; Aziz, Sandra Arifin; Andarwulan, Nuri (Balittro, 2013)
ABSTRACTBangun-bangun [Plectranthus amboinicus] is a functional vegetable that is used as lactagogue. This research was aimed to provide information of the effect of organic fertilizer on shoot, total phenolic, and anthocyanin production of bangun-bangun. This experiment was conducted at Bogor Agricultural University, Leuwikopo experimental station (Indonesia), from December 2012 to February 2013. The experiment was laid out in randomized block design with single factor with five combination of organic fertilizer treatments (combination of cow manure 12.3 t ha-1, rock phosphate 1.5 t ha-1, rice-hull ash 5.5 t ha-1) with three replications. The result showed that application of organic fertilizer increased of shoot production. Application of 12.3 t ha-1 cow manure + 1.5 t ha-1 rock phosphate + 5.5 t ha-1 rice-hull ash produced shoot dry weight ha-1 (57.33%) and metabolite production ha-1 (total phenolic 12.06%, anthocyanin 41.73%) higher than no fertilizing (P > 0.05). Application of cow manure + rock phosphate produced the lowest shoot dry weight ha-1 and metabolite production ha-1. The result of this research suggested that nitrogen, phosphorus, and potassium were needed on shoot production of bangun-bangun.Key words: Plectranthus amboinicus, phenylalanine ammonia lyase, secondary metabolite